2009
DOI: 10.1017/s1751731109004595
|View full text |Cite
|
Sign up to set email alerts
|

Growth heterogeneity in rearing sea bass (Dicentrarchus labrax): test of hypothesis with an iterative energetic model

Abstract: This study aimed at modeling the relative importance of food intake on growth heterogeneity among cultured sea bass (Dicentrarchus labrax). First, we designed an individual growth model comprising five compartments (Energy intake, Losses, Net Energy, Recovered Energy and Maintenance). This model was calibrated with a first experiment carried out in eight tanks; A total of 130 juveniles (11 g) per tank were fed by a self-feeder (84 days, 208C, 16L : 8D, 30 g NaCl/l). A second experiment was performed to better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Stocking density has been shown to affect behavioural interactions in several fish species such as intraspecific competition (Martins et al, 2005) and may influence the inter-individual variations of FI. This intraspecific competition and social hierarchy have been demonstrated on several occasions to be the driving factor behind growth heterogeneity (Campeas et al, 2009). To the best of our knowledge, thus far, such an effect has not been reported previously among tilapias, which are one of the major contributors to world aquaculture nowadays (Food and Agriculture Organization of the United Nations - FAO-FishStatPlus, 2012).…”
Section: Introductionmentioning
confidence: 82%
“…Stocking density has been shown to affect behavioural interactions in several fish species such as intraspecific competition (Martins et al, 2005) and may influence the inter-individual variations of FI. This intraspecific competition and social hierarchy have been demonstrated on several occasions to be the driving factor behind growth heterogeneity (Campeas et al, 2009). To the best of our knowledge, thus far, such an effect has not been reported previously among tilapias, which are one of the major contributors to world aquaculture nowadays (Food and Agriculture Organization of the United Nations - FAO-FishStatPlus, 2012).…”
Section: Introductionmentioning
confidence: 82%
“…In our study, this idea is supported by the fact that correlations between initial and final weights tended to be lower in T low groups, but at the end of experiment, when CV w increased, correlations reached the same values as those of the T high groups. Indeed, Campéas (2009) showed that this tendency was related to a modification of fish rank (weight rank between the beginning and the end of the studied period) in low CV w groups.…”
Section: The Effects Of a Reduction In The Body Weight Coefficient Ofmentioning
confidence: 92%
“…Indeed, in exploitation competition, there are no direct interactions between competitors; instead, one individual exploits and depletes a food patch before a second individual arrives (Ward et al 2006). Recent work based on growth heterogeneity modelling in fish rearing systems rejected the hypothesis of competition decrease within time (Campéas 2009). According to this author, growth heterogeneity stability is not correlated with the stabilisation of social interactions (i.e., size had little or no effect on fight determinism), and CV w stability is the result of the dominance pressure of large fish on small fish.…”
Section: The Effects Of a Reduction In The Body Weight Coefficient Ofmentioning
confidence: 99%
“…Growth heterogeneity between individuals appears to be the rule rather than the exception in wild and cultured fish populations (Huston & DeAngelis, 1987; Kestemont et al , 2003; Campeas et al , 2009). An individual fish has an intrinsic capacity for growth that is governed by its genome and by epigenetic factors such as yolk size of embryos.…”
Section: Introductionmentioning
confidence: 99%